Victor Papanek : designer for the real world - Clarke, Alison J. (The MIT Press, 2021)
"A cultural geneaology of the influence of Victor Papanek on the world of transdisciplinary design"- Resumé vydavatel
Keywords: Papanek, Victor J., -- 1923-1998; průmysloví designéři -- Spojené státy americké; průmyslový design -- sociální aspekty; industrial designers -- United States; industrial design -- social aspects; elektronické knihy; monografie; electronic books; monographs